KESTABILAN KOMPONEN UTAMA DENGAN BOOTSTRAP - Rachmatin, Dewi
Abstract: The stability of principal component which is learned with the bootstrap method is topics of this thesis. In this topic, we use eigenvalue and eigenvector of covariance or correlation matrix. The stability measures give a criterion allowing to answer the following question, \"which subspaces possess good insurance against instability and thus against wrong conclusions\".